Género gramatical y lengua española - Devís Márquez, P. Pablo (Verbum – Analecta Neolatina, 2018)
Grammatical gender has caused controversial discussions between linguists and between people outside linguistics. This article does absolutely not pretend to create more controversy and its goals are: (1) to suggest an alternative definition of gender as grammatical category and to define the means to express it in Spanish; (2) to deal with the incompatibility between proper noun and our concept of grammatical gender, as well as with the restrictions of pronouns with grammatical gender, and (3) at the same time as we analyse the acceptability of three arguments that usually are used to characterise Spanish as a sexist language, we propose an alternative characterisation of gender distinction in this language.